Thermophilic anaerobic digestion of palm oil mill effluent - Chin, K.K.; Wong, K.K. (Pergamon Press, 1983)
A laboratory study was carried out using the thermophilic anaerobic process to treat palm oil mill effluent containing 67,000 mg 1-1, COD, 31,800 mg 1-1 suspended solids and a pH of 4.5. Completely mixed reactors were operated to evaluate the effects of feed strength and solids retention times on the system's performance. A range of 5-35 days solids retention time was studied. COD reduction was 72% for the 5-day unit and greater than 90% for units having detention time 15 days or more. pH of all units was self adjusted to 7.4. Gas production was, in general, greater than 0.3 m3 kg-1 volatile solids feed.